Standar Pembuktian Mens Rea dalam Perkara Pembunuhan demi Kehormatan (Honor Killing) - Zul Khaidir Kadir (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
Honor killing cases raise persistent challenges in criminal law, particularly at the stage of proving mens rea. The core difficulty arises when honor-based motives are treated as substitutes for the mental element, or when family and community pressure is used to attenuate intent without strict factual scrutiny. This article aims to formulate a mens rea evidentiary standard capable of distinguishing intent formed through honor norms from claims of momentary emotion, while mapping the forms of knowledge and acceptance of fatal risk embedded in communal legitimization. The research adopts a normative legal method with a conceptual and analytical approach, grounded in mens rea doctrine and the extraction of fact-based indicators commonly found in criminal case files. The analysis demonstrates that honor motives must be treated with disciplinary restraint, functioning either as background context or as inference enhancers, but never as replacements for knowledge and volition. The article proposes a three-tiered mens rea test consisting of the assessment of knowledge of fatal consequences, acceptance of fatal risk, and consolidation of will through family communication and social control. This framework enables a structured differentiation between dolus directus, dolus indirectus, and dolus eventualis, while preventing social pressure from operating as an automatic excuse. The proposed tiered test strengthens criminal proof by anchoring intent in verifiable factual structures rather than moral or emotional narratives.